Re-envisioning Postdoctoral Training in Neuroscience: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Originally viewed as a few years of apprenticeship and an opportunity to prepare for an independent research career, postdoctoral training has progressed to a state of limbo for some researchers, with longer training durations; uncertain career prospects; and variability in the training, mentoring, and professional status across the neuroscience ecosystem. These challenges have been further exacerbated by the COVID-19 pandemic, resulting in a high level of uncertainty and stress for many postdoctoral researchers. To highlight these challenges and explore opportunities for modernizing postdoctoral training, the Forum on Neuroscience and Nervous System Disorders of the National Academies of Sciences, Engineering, and Medicine held a virtual workshop on February 16, 2021, titled Re-envisioning Postdoctoral Training in Neuroscience. This was the fourth workshop in a series, originating from the Forum's Action Collaborative on Neuroscience Training: Developing a Nimble and Versatile Workforce, designed to illuminate critical issues and catalyze a reconsideration of how neuroscience training could be designed to meet current and future workforce needs across multiple sectors. This Proceedings of a Workshop-in Brief summarizes the discussions that occurred at the workshop.
Keywords: Health and Medicine

The Postdoctoral Experience Revisited - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2014)
The Postdoctoral Experience Revisited builds on the 2000 report Enhancing the Postdoctoral Experience for Scientists and Engineers. That ground-breaking report assessed the postdoctoral experience and provided principles, action points, and recommendations to enhance that experience. Since the publication of the 2000 report, the postdoctoral landscape has changed considerably. The percentage of PhDs who pursue postdoctoral training is growing steadily and spreading from the biomedical and physical sciences to engineering and the social sciences. The average length of time spent in postdoctoral positions seems to be increasing. The Postdoctoral Experience Revisited reexamines postdoctoral programs in the United States, focusing on how postdocs are being guided and managed, how institutional practices have changed, and what happens to postdocs after they complete their programs. This book explores important changes that have occurred in postdoctoral practices and the research ecosystem and assesses how well current practices meet the needs of these fledgling scientists and engineers and of the research enterprise. The Postdoctoral Experience Revisited takes a fresh look at current postdoctoral fellows - how many there are, where they are working, in what fields, and for how many years. This book makes recommendations to improve aspects of programs - postdoctoral period of service, title and role, career development, compensation and benefits, and mentoring. Current data on demographics, career aspirations, and career outcomes for postdocs are limited. This report makes the case for better data collection by research institution and data sharing. A larger goal of this study is not only to propose ways to make the postdoctoral system better for the postdoctoral researchers themselves but also to better understand the role that postdoctoral training plays in the research enterprise. It is also to ask whether there are alternative ways to satisfy some of the research and career development needs of postdoctoral researchers that are now being met with several years of advanced training. Postdoctoral researchers are the future of the research enterprise. The discussion and recommendations of The Postdoctoral Experience Revisited will stimulate action toward clarifying the role of postdoctoral researchers and improving their status and experience.
Keywords: Policy for Science and Technology

Bridges to Independence: Fostering the Independence of New Investigators in Biomedical Research - National Research Council (The National Academies Press, 2005)
A rising median age at which PhD’s receive their first research grant from the National Institutes of Health (NIH) is among the factors forcing academic biomedical researchers to spend longer periods of time before they can set their own research directions and establish there independence. The fear that promising prospective scientists will choose other career paths has raised concerns about the future of biomedical research in the United States. At the request of NIH, the National Academies conducted a study on ways to address these issues. The report recommends that NIH make fostering independence of biomedical researchers an agencywide goal, and that it take steps to provide postdocs and early-career investigators with more financial support for their own research, improve postdoc mentoring and establish programs for new investigators and staff scientists among other mechanisms.
Keywords: Health and Medicine

Postdoctoral Training in the Biomedical Sciences: An Evaluation of NIGMS Postdoctoral Traineeship and Fellowship Programs (The National Academies Press, 1974)
Keywords: Health and Medicine

Assessment of NIH Minority Research and Training Programs: Phase 3 - National Research Council (The National Academies Press, 2005)
This report provides an assessment of NIH’s programs for increasing the participation in biomedical science of individuals from underrepresented minority groups. The report examines, using available data and the results of a survey of NIH trainees, the characteristics and outcomes of programs at the undergraduate, graduate, postdoctoral, and junior faculty levels. The report provides recommendations for improving these programs and their administration. It also recommends how NIH can improve the data it collects on trainees in all NIH research training programs so as to enhance training program evaluation.
Keywords: Education; Health and Medicine

Enhancing the Postdoctoral Experience for Scientists and Engineers: A Guide for Postdoctoral Scholars, Advisers, Institutions, Funding Organizations, and Disciplinary Societies - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2000)
The concept of postdoctoral training came to science and engineering about a century ago. Since the 1960s, the performance of research in the United States has increasingly relied on these recent PhDs who work on a full-time, but on a temporary basis, to gain additional research experience in preparation for a professional research career. Such experiences are increasingly seen as central to careers in research, but for many, the postdoctoral experience falls short of expectations. Some postdocs indicate that they have not received the recognition, standing or compensation that is commensurate with their experience and skills. Is this the case? If so, how can the postdoctoral experience be enhanced for the over 40,000 individuals who hold these positions at university, government, and industry laboratories? This new book offers its assessment of the postdoctoral experience and provides principles, action points, and recommendations for enhancing that experience.
Keywords: Education

Astronomy and Astrophysics in the New Millennium - National Research Council (The National Academies Press, 2001)
In this new book, a distinguished panel makes recommendations for the nation's programs in astronomy and astrophysics, including a number of new initiatives for observing the universe. With the goal of optimum value, the recommendations address the role of federal research agencies, allocation of funding, training for scientists, competition and collaboration among space facilities, and much more.
Keywords: Space and Aeronautics

Addressing the Nation's Changing Needs for Biomedical and Behavioral Scientists - National Research Council (The National Academies Press, 2000)
As biomedical and behavioral research progresses into new areas, the number of scientists active in various fields rises and falls, and the health needs of the U.S. population evolve, it is important to ensure that the preparation of future investigators reflects these changes. This book addresses these topics by considering questions such as the following:
Keywords: Health and Medicine

The Career Achievements of NIH Predoctoral Trainees and Fellows - Institute of Medicine (The National Academies Press, 1984)
Keywords: Health and Medicine

Personnel Needs and Training for Biomedical and Behavioral Research: 1981 Report - Institute of Medicine (The National Academies Press, 1981)
Keywords: Health and Medicine

Climbing the Academic Ladder: Doctoral Women Scientists in Academe: A Report to the Office of Science and Technology Policy - National Research Council (The National Academies Press, 1979)
Keywords: Education; Industry and Labor

Careers in Clinical Research: Obstacles and Opportunities - Institute of Medicine (The National Academies Press, 1994)
Transforming biological discoveries into medical treatment calls for a cadre of health professionals skilled in patient-oriented research. Yet many factors discourage talented persons from choosing clinical research as a profession. This new volume lays out the problem in detail, with specific recommendations to the federal government, the biotechnology and pharmaceutical industries, professional organizations, the health care industry, organized medicine, and the nation's universities and academic health centers. The volume explores
Keywords: Education; Health and Medicine

Personnel Needs and Training for Biomedical and Behavioral Research: The 1975 Report of the Committee on a Study of National Needs for Biomedical and Behavioral Personnel - Institute of Medicine (The National Academies Press, 1975)
Keywords: Health and Medicine

Advancing the Nation's Health Needs: NIH Research Training Programs - National Research Council (The National Academies Press, 2005)
The National Institutes of Health’s role in supporting research has long been recognized as a major factor in advancing the health needs in the nation and the world. The National Research Council was charged with the responsibility of periodically assessing the National Institutes of Health’s National Research Service Awards program, thus this book is the twelfth edition in the series. While the National Research Service Awards program now supports only a fraction of the training in the biomedical, clinical, behavioral, and social sciences, it sets a high standard for the training in all doctoral programs in these fields. Also included are the training needs of oral health, nursing, and health services research. This book has been broadly constructed to take into account the rapidly evolving national and international health care needs. The past and present are analyzed and predictions with regard to future needs are presented.
Keywords: Health and Medicine; Policy for Science and Technology; Education

The Next Generation of Biomedical and Behavioral Sciences Researchers: Breaking Through - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Since the end of the Second World War, the United States has developed the world's preeminent system for biomedical research, one that has given rise to revolutionary medical advances as well as a dynamic and innovative business sector generating high-quality jobs and powering economic output and exports for the U.S. economy. However, there is a growing concern that the biomedical research enterprise is beset by several core challenges that undercut its vitality, promise, and productivity and that could diminish its critical role in the nation's health and innovation in the biomedical industry. Among the most salient of these challenges is the gulf between the burgeoning number of scientists qualified to participate in this system as academic researchers and the elusive opportunities to establish long-term research careers in academia. The patchwork of measures to address the challenges facing young scientists that has emerged over the years has allowed the U.S. biomedical enterprise to continue to make significant scientific and medical advances. These measures, however, have not resolved the structural vulnerabilities in the system, and in some cases come at a great opportunity cost for young scientists. These unresolved issues could diminish the nation's ability to recruit the best minds from all sectors of the U.S. population to careers in biomedical research and raise concerns about a system that may favor increasingly conservative research proposals over high-risk, innovative ideas. The Next Generation of Biomedical and Behavioral Sciences Researchers: Breaking Through evaluates the factors that influence transitions into independent research careers in the biomedical and behavioral sciences and offers recommendations to improve those transitions. These recommendations chart a path to a biomedical research enterprise that is competitive, rigorous, fair, dynamic, and can attract the best minds from across the country.
Keywords: Education; Health and Medicine; Behavioral and Social Sciences

Personnel Needs and Training for Biomedical and Behavioral Research: 1983 Report - Institute of Medicine (The National Academies Press, 1983)
Keywords: Health and Medicine

Biomedical and Behavioral Research Scientists: Their Training and Supply: Volume III: Commissioned Papers - Institute of Medicine (The National Academies Press, 1989)
Keywords: Health and Medicine

Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Fourteenth Round - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics, Fourteenth Round evaluated submissions received in response to a Request for Proposals for Biomolecular Simulation Time on Anton 2, a supercomputer designed and built by D. E. Shaw Research (DESRES). Over the past 13 years, DESRES has made an Anton or Anton 2 system housed at the Pittsburgh Supercomputing Center available to the non-commercial research community, based on the advice of previous committees of the National Academies of Sciences, Engineering, and Medicine. As in those prior rounds, the goal of the fourteenth RFP for simulation time on Anton 2 is to continue to facilitate breakthrough research in the study of biomolecular systems by providing a massively parallel system specially designed for molecular dynamics simulations. The program seeks to continue to support research that addresses important and high impact questions demonstrating a clear need for Antons special capabilities. This document describes the work and transmits the decisions of the Committee.
Keywords: Math, Chemistry, and Physics

Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Eighth Round - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
This report describes the work of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics, Eighth Round. The committee evaluated submissions received in response to a Request for Proposals (RFP) for biomolecular simulation time on Anton 2, a supercomputer specially designed and built by D.E. Shaw Research (DESRES). Over the past five years, DESRES has made an Anton or Anton 2 system housed at the Pittsburgh Supercomputing Center (PSC) available to the non-commercial research community, based on the advice of previous National Research Council committees. As in prior rounds, the goal of the eighth RFP for simulation time on Anton 2 is to continue to facilitate breakthrough research in the study of biomolecular systems by providing a massively parallel system specially designed for molecular dynamics simulations. The program seeks to continue to support research that addresses important and high impact questions demonstrating a clear need for Anton's special capabilities. Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics, Eighth Round is the report of the committee's evaluation of proposals based on scientific merit, justification for requested time allocation, and investigator qualifications and past accomplishments. This report identifies the proposals that best met the selection criteria.
Keywords: Computers and Information Technology

Personnel Needs and Training for Biomedical and Behavioral Research: 1978 Report - Institute of Medicine (The National Academies Press, 1978)
Keywords: Health and Medicine